IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SD NEGERI JOMBOR 01 - Diah Ayu Oktavia (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2026)
This study aims to describe the implementation of the Deep Learning approach in developing critical thinking skills in mathematics at Jombor 01 Public Elementary School. The study used a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. Data validity was carried out through technical triangulation. The results showed that the implementation of Deep Learning was carried out through the stages of understanding, applying, and reflecting. Learning assisted by multiplication domino cards encouraged active student involvement in discussions, problem solving, and learning reflection. Students' critical thinking skills developed through activities analyzing information, determining solution strategies, providing logical reasons, and evaluating results. Supporting factors included teacher competence, the use of concrete media, and student participation, while inhibiting factors included time constraints and differences in student abilities. These findings indicate that the Deep Learning approach is effective in improving the quality of mathematics learning in elementary schools.